Association of the Affordable Care Act's Medicaid Expansion With 1-Year Survival Among Patients With Ovarian Cancer. Issue 6 (2nd June 2022) - Bodurtha Smith, Anna Jo; Applebaum, Jeremy; Fader, Amanda Nickles
Abstract : The Affordable Care Act's Medicaid expansion was associated with improved 1-year survival for patients with ovarian cancer. Abstract : OBJECTIVE: The Affordable Care Act's (ACA) 2014 Medicaid expansion is associated with gains in insurance and early-stage diagnosis among patients with gynecologic cancer, but its association with mortality remains unknown. This study aims to assess whether the ACA's Medicaid expansion was associated with improved survival among patients with ovarian cancer. METHODS: In this retrospective cohort study of patients with newly diagnosed ovarian cancer, we compared 1-year survival before and after 2014 Medicaid expansion in patients aged 40–64 years in Medicaid expansion states (intervention group) to patients aged 40–64 years in non–Medicaid expansion states using a difference-in-difference analysis. Results were adjusted for age, comorbidities, treatment at an academic center, and variables associated with Medicaid insurance status (race, income, high-school education, distance traveled for care, and living in a rural area). RESULTS: Our sample included 19, 558 patients with ovarian cancer: 9, 013 in Medicaid expansion states and 10, 545 in nonexpansion states. The ACA's Medicaid expansion was associated with increased 1-year survival among patients in expansion states compared with nonexpansion states (adjusted difference-in-difference 2.2%, 95% CI 0.4–4.1). After adding stage at diagnosis, the mortality difference between expansion and nonexpansion states was no longer evident. Medicaid expansion was associated with a significant improvement in 1-year survival for White patients (2.4%, 95% CI 0.4–4.4), but the difference was not significant for Black patients (1.3%, 95% CI −5.7 to 8.2) or rural patients (9.5%, 95% CI −8.0 to 26.9). CONCLUSION: The ACA's Medicaid expansion was associated with improvements in 1-year survival among patients with ovarian cancer, which was mediated by an earlier stage at diagnosis. Continued insurance expansion to nonexpansion states may improve survival and reduce disparities for patients with ovarian cancer.